ANALISIS PENERAPAN HACCP (HAZARD ANALYSIS CRITICIAL CONTROL POINT) PADA PROSES PRODUKSI FILLET IKAN KAKAP DI PT. ALAM JAYA UNTUK MENJAGA KUALITAS PRODUK - Mochamad Arda Trijayanto; Muslimin Abdulrahim (LPPM Universitas Bina Bangsa, 2023)
PT. Alam Jaya Rungkut, Surabaya is a company engaged in the fishing industry The company processes various types of aquatic products such as fish, squid and shrimp. PT Alam Jaya only processes fresh fish into semi-finished products or in frozen form only. Products that have been processed are then stored in cold storage. Product quality is something that companies need to pay attention to in carrying out the production process to maintain the safety and health of consumers when the product is marketed. The company has implemented HACCP (Hazard Analysis Crital Control Point) in the snapper fillet production process but there are still some findings such as cross-contamination, there are metals, metals in the product that can endanger consumers when the product will be marketed. The finding is a discrepancy between HACCP Standards and application in the field. From the findings obtained, it is necessary to analyze how far the company applies the HACCP system. Therefore, this study aims to evaluate HACCP performance in companies with the GAP Analysis method as a tool to assess HACCP performance. based on the results of the deviation assessment, it is known that the average deviation from the overall implementation of GMP is 19.81%, the SSOP gap is 20.49%. and the HACCP gap is 12.27%. From each assessment, improvements are made if there are parameters that are not in accordance with HACCP guidelines so that the application of HACCP is better